GENERATION-Z BUYING BEHAVIOUR IN INDONESIA: OPPORTUNITIES FOR RETAIL BUSINESSES - Eliot Simangunsong (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. Advances in information and communication technology have caused two major changes in the business world. Firstly, they have caused a wave of new companies emerge that base their business models on the internet. Secondly, they have given rise to the birth of a new group of buyers, known as Generation-Z, who level of expectation and response to consumption are different. Both of these changes -- in business model and in consumption behaviour -- have broad impacts on how companies connect with their business partners and customers. The main purpose of this study is to investigate Generation-Z’s buying behaviour and how this knowledge helps to bring new opportunities for retail business. We applied a qualitative research method through deep interview of 23 respondents.  This study finds that Generation-Z customers in Indonesia have a strong tendency to shop online; they show distinctive behaviours particularly when shopping for clothes and food & beverage. The demographic bonus that Indonesia has enjoyed since 2012 also highlights how this generation is important in business environment in the country